The relationship between residential exposure to atmospheric pollution and circulating miRNA in adults living in an urban area in northern France. (April 2023) - Hubert, Audrey; Achour, Djamal; Grare, Céline; Zarcone, Gianni; Muntaner, Manon; Hamroun, Aghiles; Gauthier, Victoria; Amouyel, Philippe; Matran, Régis; Zerimech, Farid; Lo-Guidice, Jean-Marc; Dauchet, Luc
Graphical abstract: Highlights: Air pollution is associated with the miRNA profile in a large, population sample. The miRNAs significantly associated with air pollution are involved in inflammation. miRNAs might mediate the effect of air pollution on health. miRNAs are potential biomarkers of the environmental risk. Abstract: Introduction: MicroRNAs are epigenetic regulatory factors capable of silencing the expression of target genes and might mediate the effects of air pollution on health. The objective of the present population-based study was to investigate the association between microRNA expression and long-term, residential exposure to atmospheric PM10 and NO2 . Method: We included 998 non-smoking adult participants from the cross-sectional ELISABET survey (2010–2014) in the Lille urban area of France. The mean residential annual pollution levels were estimated with an atmospheric dispersion modelling system. Ten microRNAs were selected on the basis of the literature data, together with two housekeeping microRNAs (miR-93-5p and miR-191-5p) and were quantified with RT-qPCRs. Multivariate linear regression models were used to study the association between microRNAs and air pollution. The threshold for statistical significance (after correction for the FDR) was set to p < 0.1. Results: The mean annual exposure between 2011 and the year of inclusion was 26.4 ± 2.0 µg/m 3 for PM10 and 24.7 ± 5.1 µg/m 3 for NO2 . Each 2 µg/m 3 increment in PM10 exposure was associated with an 8.6% increment (95%CI [3.1; 14.3]; pFDR  = 0.019) in miR-451a expression. A 5 µg/m 3 increment in NO2 exposure was associated with a 5.3% increment ([0.7; 10]; pFDR  = 0.056) in miR451a expression, a 3.6% decrement (95%CI [-6.1; −1.1]; pFDR  = 0.052) in miR-223-3p expression, a 3.8% decrement (95%CI[-6.8; −0.7]; pFDR  = 0.079) in miR-28-3p expression, a 4.3% decrement (95%CI [-7.7; −0.8]; pFDR  = 0.055) in miR-146a-5p expression, and a 4.0% decrement (95% CI[−7.4; −0.4]; pFDR  = 0.059) in miR-23a-5p expression. The difference between the two housekeeping microRNAs miR-93-5p and miR-191-5p was also associated with PM10 and NO2 exposure. Conclusion: Our results suggest that circulating miRNAs are potentially valuable biomarkers of the effects of air pollution.